Factors Influencing the Enhancement of Work Motivation among Tour Guides: A Study in Ho Chi Minh City, Vietnam - Hoa, Le Thi Kim; Khanh, Pham Ngoc (International Review of Management and Marketing, 2025)
To improve the motivation of tour guides in Ho Chi Minh City, this study will identify the elements that affect their motivation at work and offer potential solutions. A mixed-method strategy that included quantitative questionnaire surveys and qualitative expert interviews was used to accomplish this goal. Using SPSS 26 software, data from 487 tour guides actively working in Ho Chi Minh City were gathered and examined using linear regression, exploratory factor analysis (EFA), and Cronbach’s Alpha reliability assessment. According to the results, domestic tour guides’ motivation at work is greatly influenced by four major factors: (1) pay, (2) workplace culture, (3) prospects for advancement, and (4) corporate policies. The study suggests several workable ways to enhance these influencing elements in light of these findings, boosting tour guides’ motivation and productivity on the job. Government officials and travel agencies may use the study’s practical implications to create strategies to effectively cultivate a workforce of skilled tourists who can satisfy the demands of global integration.